Twinkle, twinkle, little star - Dean, James, 1957- (New York: Harper, 2014)
Youngsters are invited to join Pete the Cat as he stars in the classic nighttime song "Twinkle, Twinkle, Little Star.".
K-3
AD650L
2.7
Keywords: Children's songs, English -- United States -- Texts; Nursery rhymes, English; Cats -- Juvenile fiction; Songs; Nursery rhymes; Cats -- Songs and music; Children's songs, English -- United States; Children's songs -- Texts; Nursery rhymes, English; Cats -- Fiction; Songs